دراسة توزع كثافة التيار الكلية للفرايت – Co Zn في المجال الترددي(1kHz – 1GHz) (Latakia University Journal -Basic Sciences Series, 2014)
درس في هذا العمل توزع كثافة التيار الكلي لقرص محُضِّر من الفرايت Co(1-x) Znx Fe2 O4 حيث (x = 0.4) بالطريقة السيراميكية التقليدية بتابعية نصف قطره، وذلك في المجال الترددي (1kHz – 1GHz) بعد إدخال نصف قطر القرص، والناقلية الكهربائية والنفاذية المغناطيسية النسبية في الحسابات عند درجة حرارة الغرفة.  وتبيّن أن كثافة التيار تتركّز على السطح الجانبي للقرص عند التردد 1GHz بينما تبقى ثابتة تقريبا عند الترددات الأخرى. In this work the study of the total current density distribution for Co(1-x)ZnxFe2O4 ferrite disc where (x=0.4) prepared by using traditional ceramic method as a function of disc radius in the frequency range (1kHz – 1GHz). For achievement of this investigation the disc radius and thickness, electrical conductivity and relative magnetic permeability have been used at room temperature. It is noticed that the total current density becomes concentrated on the outer lateral surface of the disc at 1GHz frequency while it almost stays constant and nearly equals one at other frequencies of the range.